DAMPAK PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT TERHADAP TINGKAT PENDAPATAN PEDAGANG KAKI LIMA DI DESA KEDIRI KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - Iwan Muhadi (Fakultas Ekonomi Universitas Islam Al-Azhar, 2022)
A pandemic is an epidemic that spreads simultaneously everywhere, covering a wide geographic area. Disease outbreaks that fall into the pandemic category are diseases that are contagious and have a continuous line of infection. COVID-19 has been designated by the WHO as a pandemic because of its worldwide spread. The spread of Covid-19 in Indonesia has had a huge impact on the economy, so the Government has implemented the Enforcement of Restrictions on Community Activities or PPKM for short. PPKM is the policy of the Government of Indonesia since early 2021 to deal with the Covid-19 pandemic in Indonesia.Prior to the implementation of PPKM, the government had implemented Large-Scale Social Restrictions (PSBB) which took place in a number of regions in Indonesia. One of the perpetrators of Micro and Small Enterprises, the informal sector that has felt a significant impact from the Covid-19 pandemic is Street Vendors (PKL). This study aims to determine whether the implementation of Community Activity Restrictions (PPKM) has an impact on the income level of street vendors in Kediri Village, Kediri District, West Lombok Regency. This research is a type of quantitative research with an associative approach. The tabulation data is processed with the help of the IBM SPSS Statistics 20 program software. The results of this study indicate that there is a significant effect on the Implementation of Community Activity Restrictions or PPKM on the income level of Street Vendors (PKL) in Kediri Village, Kediri District, West Lombok Regency.